2020
DOI: 10.1016/j.jiph.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies reveal mechanism by which quinone derivatives can inhibit SARS-CoV-2. Study of embelin and two therapeutic compounds of interest, methyl prednisolone and dexamethasone

Abstract: Background Quinones are reactive to proteins containing cysteine residues and the main protease in Covid-19 contains an active site that includes Cys145. Embelin, a quinone natural product, is known to have antiviral activity against influenza and hepatitis B. Preliminary studies by our group also indicate its ability to inhibit HSV-1 in cultured cells. Methods Docking and DFT methods applied to the protease target. Results a mechanism for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 51 publications
(61 reference statements)
0
47
0
Order By: Relevance
“…The anti-inflammatory activity of celastrol is associated with down-regulation of NF-kB pathway mediated by suppression of IKK activation (SETHI et al, 2006), probably due to the formation of Michael’s adduct between its quinone methide and Cys179 from IKK 80,84 . In silico studies have reported that other quinone derivatives exhibit antiviral properties associated with the ability to form Michael’s adduct 85 , such as the glucocorticoids methylprednisolone and dexamethasone used to treat severe Covid-19 patients 86,87 .…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory activity of celastrol is associated with down-regulation of NF-kB pathway mediated by suppression of IKK activation (SETHI et al, 2006), probably due to the formation of Michael’s adduct between its quinone methide and Cys179 from IKK 80,84 . In silico studies have reported that other quinone derivatives exhibit antiviral properties associated with the ability to form Michael’s adduct 85 , such as the glucocorticoids methylprednisolone and dexamethasone used to treat severe Covid-19 patients 86,87 .…”
Section: Discussionmentioning
confidence: 99%
“…The covalent bond between the quinone carbonyl and the thiolate of Cys145 was hypothesized. To help this reaction mechanism, His41 captured the hydrogen atom from Cys145 that became prone to release a proton to the carbonyl quinone engaged with the thiolate [146]. preceded by curcumin [143,144].…”
Section: Benzoquinonesmentioning
confidence: 99%
“…To help this reaction mechanism, His41 captured the hydrogen atom from Cys145 that became prone to release a proton to the carbonyl quinone engaged with the thiolate [146]. By computational methods was observed that emodin (Figure 18b) binds Asp67, Ala71, and Lys74 residues of ACE2 receptor, and Asn448, Ala464, Val472, and Gly474 residues of Spike protein [147].…”
Section: Benzoquinonesmentioning
confidence: 99%
“… Group [Ref] Target Database/natural compounds (n) Methodology Outcome (best in silico leads) Ghosh et al ., ( Ghosh et al, 2021 ) M pro 113 Compounds of natural origin inhibiting M pro in SARS-CoV were retrieved, and 88 compounds were further considered for current work on the basis of available IC 50 and binding affinity data QSAR based data mining followed by structural and physiochemical interpretation (SPCI) analysis Rutin, Hespiridine, 22-Hydroxyhopan-3-one, Oolonghomobisflavan-A, Theasinensin-D, Quercetin, 3-vicianoside, Deacetylcentapicrin, Kouitchenside, Neohesperidin, Lignan, Myricitrin, Baicalin, Cyanidin 3-glucoside Cheke et al ., ( Cheke et al, 2020 ) Spike glycoproteins and ACE2 12 Natural compounds with reported antiviral attributes Molecular docking Indigo blue, glycyrrhizin, β-sitosterol, indirubin, bicylogermacrene, curcumin, hesperetin, rhein, and berberine Sahin et al ., ( Sahin et al, 2021 ) M pro Didemnins A, B and C Molecular docking Didemnin B Monajjemi et al ., ( Monajjemi et al, 2020 ) Protease Vidarabine, Cytarabine, Gemcitabine, and Matrine extracted from Gillan's leaves plants. Docking simulation and NMR investigation Cytarabine Saeed et al ., ( Saeed et al, 2020 ) Endoribonuclease NSP15 1624 Natural compounds (NuBBE database) Virtual screening and molecular docking, followed by molecular dynamics for top leads NuBBE-1970 and NuBBE-242 Caruso et al ., ( Caruso et al, 2020 ) M pro Quinone derivatives Molecular docking and DFT Embelin Basu et al ., ( Basu et al, 2020 ...…”
Section: Studies Based On Natural Products or Naturally Derived Drugsmentioning
confidence: 99%